2018
DOI: 10.3897/zse.94.28765
|View full text |Cite
|
Sign up to set email alerts
|

Redescription and reassignment of Ondina semicingulata to the Pyramidellidae, with review of the occurrence of genus Evalea in the Western Atlantic (Gastropoda)

Abstract: ActeonsemicingulatusDall, 1927, previously known only by its original description is reassigned to the Pyramidellidae, inOndina, based on the collecting of several new specimens along the coast of Brazil, in the same bathymetry as the type locality. Its shell shape variation is discussed and Odostomia (Evalea) ryclea Dall, 1927 is considered a synonymy. Other Western Atlantic species, previously allocated to other genera are transferred toOndina:AclisstriataVerrill, 1880, Odostomia (Iolaea) hendersoni Bartsch,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Pyramidellidae is one of the most diversified families of gastropods. In the last years, several studies performed in different areas, have greatly improved the knowledge on this family (e.g., Schander, 1994;van Aartsen et al, 1998van Aartsen et al, , 2000Lygre et al, 2011;Pimenta et al, 2008Pimenta et al, , 2018Høisaeter, 2014;and references therein). These studies frequently showed that numerous pyramidellid species are found co-existing in particular, even small, geographic areas, as well as the fact that a high number of species have remained undescribed until recent times, a phenomenon particularly noticeable when considering the fauna from South America (Pimenta, 2012;Pimenta & Absalão, 2001, 2004Pimenta et al, 2008Pimenta et al, , 2009Güller & Zelaya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Pyramidellidae is one of the most diversified families of gastropods. In the last years, several studies performed in different areas, have greatly improved the knowledge on this family (e.g., Schander, 1994;van Aartsen et al, 1998van Aartsen et al, , 2000Lygre et al, 2011;Pimenta et al, 2008Pimenta et al, , 2018Høisaeter, 2014;and references therein). These studies frequently showed that numerous pyramidellid species are found co-existing in particular, even small, geographic areas, as well as the fact that a high number of species have remained undescribed until recent times, a phenomenon particularly noticeable when considering the fauna from South America (Pimenta, 2012;Pimenta & Absalão, 2001, 2004Pimenta et al, 2008Pimenta et al, , 2009Güller & Zelaya, 2019).…”
Section: Introductionmentioning
confidence: 99%